2012
DOI: 10.1073/pnas.1120237109
|View full text |Cite
|
Sign up to set email alerts
|

Co-transplantation of pure blood stem cells with antigen-specific but not bulk T cells augments functional immunity

Abstract: Impaired immunity is a fundamental obstacle to successful allogeneic hematopoietic cell transplantation. Mature graft T cells are thought to provide protection from infections early after transplantation, but can cause life-threatening graft-vs.-host disease. Human CMV is a major pathogen after transplantation. We studied reactivity against the mouse homologue, murine CMV (MCMV), in lethally irradiated mice given allogeneic purified hematopoietic stem cells (HSCs) or HSCs supplemented with T cells or T-cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Co-transplantation with purified HSC and T cell subpopulations with targeted anti-tumor or anti-pathogen activity may be a useful strategy for providing stem cell replacement and rapid disease-specific functional immunity to improve outcomes. As a proof-of-concept example of this approach, Müller and colleagues recently demonstrated transplantation of mice with purified allogeneic HSC plus tetramer-selected T cells directed against murine cytomegalovirus (MCMV) [49*]. Massive expansion of functional anti-MCMV specific T cells with enhanced anti-viral immunity was observed in comparison with recipients of HSC plus unselected T cells.…”
Section: Graft Preparation: Purified Allogeneic Hsc Transplantationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-transplantation with purified HSC and T cell subpopulations with targeted anti-tumor or anti-pathogen activity may be a useful strategy for providing stem cell replacement and rapid disease-specific functional immunity to improve outcomes. As a proof-of-concept example of this approach, Müller and colleagues recently demonstrated transplantation of mice with purified allogeneic HSC plus tetramer-selected T cells directed against murine cytomegalovirus (MCMV) [49*]. Massive expansion of functional anti-MCMV specific T cells with enhanced anti-viral immunity was observed in comparison with recipients of HSC plus unselected T cells.…”
Section: Graft Preparation: Purified Allogeneic Hsc Transplantationsmentioning
confidence: 99%
“…Massive expansion of functional anti-MCMV specific T cells with enhanced anti-viral immunity was observed in comparison with recipients of HSC plus unselected T cells. De novo T cell immunity arising from the donor HSC was also significantly improved [49*], indicating this strategy may lead to better qualitative immune recovery than with unmanipulated grafts that involve crude whole T cell adoptive transfer.…”
Section: Graft Preparation: Purified Allogeneic Hsc Transplantationsmentioning
confidence: 99%
“…The data in (C) represent total percentage; one way ANOVA was performed, where *p % 0.05 and **p % 0.01. Data and error bars in (D), (E), and (G) represent means ± SD; one-way ANOVA was performed, where *p % 0.05, **p % 0.01, and ***p % 0.001. host, resulting in potentially lethal organ damage as well as immune deficiency caused by lymphoid organ homing donor T cells (Gallatin et al, 1986;Krensky et al, 1990;Weissman, 2000;Tsao et al, 2009;M€ uller et al, 2012a). GvHD can be avoided by transplanting purified HSCs, which lack mature T cells (Shizuru et al, 1996;Uchida et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that common virus specific memory T cells including EBV-specific and CMV-specific memory T cells do not GVHD in humans (711). However, since alloreactive memory T cells can be generated either by cross-reaction or allospecific memory reaction, it is important to further understand the biology and pathogenesis of the true allospecific memory T cells in GVHD.…”
Section: Introductionmentioning
confidence: 99%